SUSTAINABILITY MARKETING, DITINJAU DARI INOVASI BISNIS, SIKAP KONSUMEN DAN LOYALITAS (STUDI PADA PT. KERETA API INDONESIA DAOP VI YOGYAKARTA) - Annisa Octavia; Istiatin Istiatin; Djumali Djumali (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study was to determine whether there is a significant influence between the variables of business innovation, consumer attitudes, and loyalty to sustainability marketing. In addition, it is also to determine whether there is a significant simultaneous influence and which variable is the most dominant in influencing sustainability marketing at PT. Indonesian Railways DAOP VI Yogyakarta. The method used is descriptive quantitative method. The population in this study is not infinite and the sample used is 100, where the sampling technique uses accidental sampling. The data used are primary data and secondary data with data collection techniques: observation, documentation, questionnaire and literature study. The data analysis technique in this study used multiple linear tests. The results of the study can be concluded that: The results of the study can be concluded that: 1) There is an effect of business innovation, consumer attitudes, and loyalty simultaneously on sustainability marketing at PT. Kereta Api Indonesia DAOP VI Yogyakarta, 2) There is an effect of business innovation on sustainability marketing at PT. Kereta Api Indonesia DAOP VI Yogyakarta, 3) There is an influence of consumer attitudes on sustainability marketing at PT. Kereta Api Indonesia DAOP VI Yogyakarta, 4) There is an effect of loyalty on sustainability marketing at PT. Indonesian Railways DAOP VI Yogyakarta. Keywords: Sustainability Marketing, Business Innovation, Consumer Attitudes, Loyalty